Moral judgment competence of nursing students in the Czech Republic - Bužgová, Radka; Sikorová, Lucie (Nurse education today, 2013)
The aim of this cross-sectional study was to determine the level of moral judgment competence in students of nursing at the University of Ostrava Faculty of Medicine, and whether it is influenced by the field of study, type of study, current year of study and age. The design of the study was cross-sectional. The survey sample comprised 662 full-time and part-time students of General Nursing and Midwifery. To measure ethical competence, Lind's Moral Judgment Test (MJT, 1995) was used. The nursing students showed low C-index scores (the mean C-index was 14.24 ± 9.56). The C-index was significantly influenced only by the type of study and age (p<0.05). Part-time students and those over 30 years of age had the lowest C-index scores. On average, the students preferred stages 5 and 6 of moral judgment, that is the post-conventional level. Due to the nursing students' lower C-index scores, methods developing ethical argumentation should be introduced into nursing ethics courses.
Keywords: Middle Aged; lidé středního věku; Adult; mužské pohlaví; ošetřovatelská etika; Nursing students; průzkumy a dotazníky; Judgment; Cross-Sectional Studies; Moral judgment test; dospělí; Humans; Morals; Ethics, Nursing; lidé; Students, Nursing; Surveys and Questionnaires; Attitudes; Moral competence; mínění; Czech Republic; Female; Age Factors; Česká republika; studenti ošetřovatelství; Euthanasia; ženské pohlaví; mravy; Male; věkové faktory; průřezové studie